ANALISIS PENGARUH PENGETAHUAN KEUANGAN,SIKAP KEUANGAN, PERILAKU KEUANGAN, KONTROL DIRI, DAN AKSES INFORMASI KEUANGAN TERHADAP LITERASI KEUANGAN - Amira Nanda Arianni; Hwihanus (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of financial knowledge, financial attitudes, financial behavior, self-efficacy, and access to financial information through financial technology on the financial literacy of students at the University of 17 August 1945 Surabaya. This research employs a quantitative approach with an explanatory research design to examine the causal relationships among variables, including the moderating role of financial education. Data were analyzed using statistical testing and bootstrapping techniques to assess both direct and indirect effects. The results indicate that financial attitude has a significant influence on students’ self-efficacy. In contrast, financial knowledge and financial behavior do not show significant effects on either self-efficacy or financial literacy. Furthermore, self-efficacy is found to significantly enhance financial literacy, suggesting that students’ confidence in managing their finances is a key factor in strengthening their financial literacy. Meanwhile, financial education does not significantly moderate the relationships among the financial variables examined. Overall, the findings demonstrate that financial literacy improvement is not solely determined by knowledge, but is more strongly influenced by financial attitudes and students’ self-confidence in making financial decisions.